Dynamic hip screws versus cannulated screws for femoral neck fractures: a systematic review and meta-analysis - Li, Lang (J Orthop Surg Res, 2020)
OBJECTIVE: Dynamic hip screw (DHS) and cannulated screws (CS) are widely used for femoral neck fractures. However, there is no definite result as to which surgical method bring less complications. We performed this study to compare the complication (mortality, non-union, avascular necrosis (AVN), and revision) of DHS and CS for the treatment of femoral neck fractures patients. METHODS: We searched Pubmed, Ovid, Cochrane Central Register of Controlled Trials, and other relevant studies related the comparison of DHS versus CS for femoral neck fractures from inception to Jan 7, 2020. The quality of the included randomized controlled trials (RCTs) and retrospective studies were assessed using the Cochrane Collaboration tool and Newcastle-Ottawa (NOS), respectively. The meta-analysis was performed by the RevMan 5.2 software. RESULTS: Nine RCTs and seven retrospective cohort studies were included for meta-analysis. CS was found to be superior to DHS with respect to AVN rate (OR 1.47; 95% CI 1.08–1.99; p = 0.01, I(2) = 0%). There were no significant between-group differences with respect to mortality, non-union, and revision (p > 0.05). CONCLUSION: DHS and CS have similar complication including mortality, revision rate, and non-union, but CS has superior to DHS on ANV. However, further studies are required to provide more robust evidence owing to some limitations.